PEMODELAN CLUSTERWISE LINEAR REGRESSION UNTUK IDENTIFIKASI FAKTOR YANG MEMENGARUHI PREVALENSI STUNTING DI JAWA TENGAH - Berliana Ercha Pratiwi; Anton Saputro; Afifa Nur Mila; Moch. Abdul Mukid; Masithoh Yessi Rochayani (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2026)
Sustainable development in the Sustainable Development Goals (SDGs) emphasizes health as a key pillar, including in overcoming malnutrition that causes stunting. Central Java Province recorded a stunting prevalence rate of 20.7% in 2023, so it is necessary to analyze the factors that influence this condition. This study uses the Clusterwise Linear Regression (CLR) method to identify factors that contribute to the prevalence of stunting based on regional characteristics. The variables analyzed include the percentage of low birth weight babies (LBW), mothers who exclusively breastfeed less than six months, women who marry at an early age, households with proper sanitation, households with clean water sources, and households that have a Prosperous Family Card (KKS). The results showed that there were 3 optimal clusters. The coefficient of determination for each cluster was 99.52% for cluster 1, 99.76% for cluster 2, and 98.26% for cluster 3.